Development of a strategy to define the orientation of a deposition tool in 3D printing tasks - simulation in Matlab and realization in RobotStudio - Ascenso, Francisco José Ribeiro (2020)
Dissertação de Mestrado Integrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia